ASSESSMENT OF GENETIC VARIABILITY PARAMETERS IN MAGIC POPULATION OF SOYBEAN [Glycine max (L.) MERRILL] - BIDUSH RANJAN SWAR; V. SWARNA LATHA; M. RAJENDAR REDDY; S. VANISRI (The Bioscan, 2020)
The present investigation was carried out to assess the genetic variability present in 95 soybean MAGIC lines along with six checks for 10 different quantitative traits. The analysis of variance revealed significant variation among all the characters. The higher estimates of PCV and GCV were found for seed yield plant -1 (29.1, 27.3), pods plant -1 (28.9, 27.5) and the number of branches plant -1 (23.9, 23.2) and a lower value was observed for protein content (3.94, 3.36) and oil content (6.9, 6.56). The measure of broad sense heritability was found high for most of the traits and the lowest (51.4 %) for harvest index. High heritability coupled with high genetic advance was observed for number of pods plant -1 , number of branches plant -1 , seed yield plant -1 and 100 seed weight indicating that these traits are governed by additive gene effects and direct selection of soybean MAGIC lines based on these traits would be effective.